Experimentally Induced Preterm Birth in Sheep Following a Clinical Course of Antenatal Betamethasone: Effects on Growth and Long-Term Survival. (August 2017) - Nguyen, Vivian B.; De Matteo, Robert; Harding, Richard; Stefanidis, Aneta; Polglase, Graeme R.; Black, M. Jane
Preterm births account for approximately 10% of births worldwide, with the majority (∼80%) being moderate preterm. Our aim was to determine the effects of moderate preterm birth on survival and long-term growth of male and female offspring using an ovine model of preterm birth that was preceded by a clinically relevant dose of corticosteroids. Ewes were induced to deliver preterm or at term; those assigned to deliver preterm were administered antenatal betamethasone (11.4 mg, 2 doses, 24 hours apart). The growth (body weight and body dimensions) of offspring was monitored to adulthood (62 weeks) when the animals were humanely killed for organ collection. Survival in the immediate period following preterm birth was high (75% for both sexes). However, there were unexpected deaths between 5 and 12 weeks of age, as a result of vitamin E/selenium deficiency; this only occurred in preterm offspring. From birth until adolescence, preterm lambs were lighter than term lambs (controls). After this time, there was gradual catch-up in body weight in preterm females, whereas in preterm males, body weight remained lower than in controls. Preterm sheep were smaller in stature than controls throughout life. This clinically relevant model of preterm birth leads to equally high survival rates in both sexes and is an excellent animal model in which to examine the effects of moderate preterm birth on growth and development of organ systems into adulthood.